1983
DOI: 10.1002/cber.19831161104
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung und Molekülstruktur von Tris(dimethyldithiocarbamato)aluminium, eine Verbindung mit hexakoordiniertem Aluminium

Abstract: AI(NR,), und ClAI(NR,), (R = CH,) addieren CS, unter Bildung der Dimethyldithiocarbamate 1 und 2, von denen 1 in Benzol monomer, 2 hingegen dimer ldslich ist. 27Al-NMR-Daten weisen hexakoordinierte Al-Atome aus, die durch die Rontgenstrukturanalyse von 1 bestatigt werden: das Al-Atom ist verzerrt trigonal antiprismatisch von sechs Schwefelatomen umgeben. Die C2NCS2-Gruppen sind planar. Fur 2 folgt eine Struktur mit zwei briickenstandigen C1-Atomen, jeweils vier S-Atome erganzen zur Hexakoordination der zwei Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…A single-crystal X-ray structure determination for Al(S 2 CNMe 2 ) 3 confirmed the formation of an unusual six coordinate aluminum center with bidentate dithiocarbamate chelation. [18] In close parallel to the present study, we have also previously observed CO 2 insertion in Al-N bonds in tmpAl fragments. [5,8] With the (amino)(phosphanyl)alumane, 2, the question of interest was: will this reagent, with both Al-N and Al-P bonds, undergo selective insertion or insertion in all Al-N and Al-P bonds?…”
Section: Synthesis and Reactionssupporting
confidence: 85%
See 3 more Smart Citations
“…A single-crystal X-ray structure determination for Al(S 2 CNMe 2 ) 3 confirmed the formation of an unusual six coordinate aluminum center with bidentate dithiocarbamate chelation. [18] In close parallel to the present study, we have also previously observed CO 2 insertion in Al-N bonds in tmpAl fragments. [5,8] With the (amino)(phosphanyl)alumane, 2, the question of interest was: will this reagent, with both Al-N and Al-P bonds, undergo selective insertion or insertion in all Al-N and Al-P bonds?…”
Section: Synthesis and Reactionssupporting
confidence: 85%
“…The spectra for 2-4 can be compared with data for 1 and tmp 2 AlPPh 2 , [5] and the spectra for 5-8 can be examined against data for [MeAl-(O 2 Ctmp) 2 ] 2 , [5] [(tBuAl) 2 - [8] and Al(S 2 CNMe 2 ) 3 . [18] In each of the new compounds 2-8, the 1 H and 13 C{ 1 H} spectra are consistent with a single tmp group environment with free rotation about the Al-N bonds and rapid ring inversion. These spectra also show a single Me 3 Si or Me 3 Sn environment.…”
Section: Nmr Characterizationmentioning
confidence: 54%
See 2 more Smart Citations
“…In addition, the average AlϪS bond length Al (6) ϪS (2) has been found to be 2.399 Å . [22] (Coordination numbers are set here in superscript). Therefore, we observe an increase in the AlϪS bond lengths as the coordination number of sulfur increases.…”
Section: Discussionmentioning
confidence: 99%